Living with non‐cardiac chest pain - An inductive qualitative interview study of spouses' perspectives - Magda Eriksson‐Liebon; Anita Kärner Köhler; Peter Johansson; Ghassan Mourad (Wiley, 2024)
Abstract Aim To explore spouses' experiences of living with a partner suffering from non‐cardiac chest pain (NCPP). Design An inductive qualitative study. Methods Individual interviews (n = 10) were performed with spouses of partners having NCCP and cardiac anxiety. The analysis was performed according to Patton's guide for content analysis of qualitative data. Results Three categories and seven subcategories were identified. First, 'a feeling of being neglected', where spouses felt ignored by healthcare professionals and excluded by their partners. Secondly, 'a tension between hope and despair' encompassed feelings of faith, support, unpreparedness for chest pain and situational frustration. Lastly, in 'a threat to ordinary life', spouses noted chest pain‐induced changes impacting daily life, finances, leisure and relationships. To conclude, NCCP in partners significantly affects their spouses emotionally and practically. Spouses felt neglected and isolated, oscillating between hope and despair and experiencing faith, powerlessness and frustration. They also faced challenges in daily life and relationships.